OPTIMALISASI PENDAMPINGAN PROSES SERTIFIKASI HALAL UMK DI CIREBON - mahrun nisa ali (UIN Siber Syekh Nurjati Cirebon, 2023)
Halal certification will be mandatory for all products in Indonesia including MSEs products. That is why the acceleration of halal certification must be carried out by BPJPH, one of which is by forming a companion team for the halal product process for MSEs. The purpose of this study was to analyze the optimization of MSEs coaching in submitting halal certificates in Cirebon. The research method used is through a qualitative approach with interactive model analysis method, using primary and secondary data sourced from observation, interviews and literature review. The results of this study indicate that LP3H IAIN Syekh Nurjati Cirebon has assisted MSEs a lot in applying for halal certification, but there are still some obstacles in it. With this effort, it is hoped that it will be able to resolve the obstacles encountered so that the assistance of MSEs in applying for halal certificates in Cirebon becomes more optimal.